Wearable cardioverter-defibrillator after myocardial infarction - Olgin, Jeffrey E.; Borggrefe, Martin (The New England journal of medicine, 2018)
Original Article from The New England Journal of Medicine — Wearable Cardioverter-Defibrillator after Myocardial Infarction